Investigations of Crucial Factors for the Non-Covalent Functionalization of Black Phosphorus (BP) using Perylene Diimide Derivatives for the Passivation of BP Nanosheets - Eisenkolb, Jasmin; Lloret, Vicent; Zink-Lorre, Nathalie; Pla, Sara; Abellán, Gonzalo; Sastre-Santos, Ángela; Hauke, Frank; Fernández-Lázaro, Fernando; Hirsch, Andreas (Chemistry - A European Journal, 2024)
The non-covalent functionalization of black phosphorus (BP) was studied with a scope of ten tailor-made perylene diimides (PDIs). A combination of UV/Vis-, fluorescence-, as well as Raman spectroscopy and atomic force microscopy was used to investigate the structural factors, which contribute to a pronounced PDI-BP interaction and thus support the protection of BP nanosheets against oxidative degradation. We were able to show, that water-soluble, amphiphilic PDIs with highly charged head groups can be used for the non-covalent functionalization of BP in aqueous media. Here, based on the hydrophobic effect, an efficient adsorption of the respective PDI molecules takes place and leads to the formation of a passivating film, yielding a considerable stabilization of the BP flakes under ambient conditions exceeding 30 days.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Non-covalent functionalization; Passivation; Perylene diimides; Phosphorus; Supramolecular chemistry